Surfaces contamination with 5-Fluorouracil in two Portuguese hospitals - Viegas, Susana (2014)
During the last years there has been an increasing concern about occupational exposure to cytostatic drugs in hospitals. The first findings on occupational exposures among hospital personnel administering chemotherapy were reported only in 1979. Since then, a great number of studies have been publishing describing possible exposure-related health effects. Consequently, rigorous guidelines for the safe handling of cancer chemotherapeutic agents were devised and the handling facilities in hospitals were extensively improved. However, recent studies developed in European countries revealed detectable amounts of several drugs in surface wipe samples. Dermal absorption after contact with contaminated surfaces can play an important role in exposure to antineoplastic drugs. Therefore, the existence of contamination in workplace surfaces implies an increased risk of exposure for health care workers. Since there is no recent report in Portugal, regarding the occupational exposure to antineoplastic drugs, a study was developed aiming to determine the 5-fluorouracil (5-FU) contamination on work surfaces of two Portuguese hospitals.